EFFECT OF DOXORUBICIN THERAPY ON TRANSMISSIBLE VENEREAL TUMOUR IN DOGS - GANDHIMATHI, D; GURUPRIYA, G; ARIVUSELVAN, P; SRIDEVI, P; JOSEPH, CECILIA (The Indian Journal of Animal Reproduction, 2011)
The efficacy and toxicity of doxorubicin therapy on transmissible venereal tumors in dogs in comparison with vincristine was studied. Vincristine at the dose rate of 0.025 mg/kg intravenously resulted in complete remission of tumour in five of six cases giving 83.33 per cent success rate while Doxorubicin at a dose rate of 30 mg/m2 intravenously caused complete remission of tumour mass in five of the six cases (83.33) and partial remission in one. The side effects such as anorexia, vomiting commonly seen with vincristine administration was minimal with doxorubici n hydrochloride.